The Effects of Product Variety and Price Perception on Purchase Decisions: Evidence from ROSCA Tumbler Consumers on the Shopee Marketplace - Aini Nabilah Marzuq; Damajanti Sri Lestari; Liling Listyawati; Dian Ferriswara (International Journal of Economics, Commerce, and Management, 2026)
The rapid growth of digital marketplaces has fundamentally transformed consumer decision-making processes by intensifying price transparency, product comparability, and information exposure. In highly competitive marketplace environments, consumers are frequently confronted with numerous product alternatives and dynamic pricing structures, which shape how they evaluate options and ultimately decide to purchase. This study examines the effects of product variety and price perception on consumers’ purchase decisions in the context of ROSCA tumbler products sold on the Shopee marketplace. Using a quantitative explanatory approach, this research employs a survey-based design to analyze the relationships among variables and to estimate their relative effects through multiple linear regression analysis. Data were collected from 100 respondents who had previously purchased ROSCA tumblers on Shopee, selected using purposive sampling based on predefined criteria. The research instrument consisted of 15 Likert-scale items measuring product variety, price perception, and purchase decision. Data analysis included descriptive statistics, instrument validity and reliability testing, regression assumption diagnostics, and hypothesis testing using both partial (t-test) and simultaneous (F-test) procedures. The findings reveal that product variety has a positive and significant effect on purchase decisions, indicating that consumers are more likely to finalize purchases when they perceive product options as sufficiently diverse, relevant, and comparable. Price perception also exerts a positive and significant influence and demonstrates a stronger relative effect compared to product variety. This result underscores the central role of perceived price fairness, competitiveness, and value-for-money in shaping purchase decisions within transparent and highly competitive marketplace settings. Simultaneously, product variety and price perception explain a substantial proportion of variance in purchase decisions, highlighting their combined importance as key marketing stimuli. These findings contribute to the literature on digital consumer behavior by providing empirical evidence from a specific marketplace–product context and offer practical implications for sellers and brand managers in optimizing assortment design and pricing strategies to enhance conversion rates in online marketplaces